Ustavno sodišče de constitutione ferenda - o predlogu za spremembo 160., 161. in 162. člena Ustave RS iz leta 2023 - Bardutzky, Samo (Podjetje in delo, 2024)
The article aims to evaluate the government proposal for the constitutional reform pertaining to the position and jurisdiction of the Constitutional Court of Slovenia. The starting points of the evaluation process are the clearly defined objective of the constitutional reform and the requirement for the coherence of the constitutional text. The article focusses on two elements of the constitutional reform: the redefinition of the jurisdiction of the Constitutional Court and the new rules on privileged applicants in the review of general acts.